Inequality in Electricity Consumption and Economic Growth: Evidence from a Small Area Estimation Study - Cuong Viet Nguyen; Khuong Duc Nguyen; Tuyen Quang Tran (Global Labor Organization (GLO), 2021)
Our study uses a small area estimation method to estimate the average and inequality of per capita kWh consumption for small areas in Vietnam. It shows evidence of a large spatial heterogeneity in the electric power consumption between districts and provinces in Vietnam. Households in the mountains and highlands consumed remarkably less electricity than those in the delta and coastal areas. Notably, we find a U-shaped relationship between the inequality of electricity consumption and economic levels in Vietnam. In poor districts and provinces, there is very high inequality in electricity consumption. Inequality is lower in middle-income districts and provinces.
Keywords: O13; Q43; D63; 330; Electricity consumption; Energy inequality; Economic growth; Small area estimation; Vietnam